2013
DOI: 10.1152/ajprenal.00478.2012
|View full text |Cite
|
Sign up to set email alerts
|

The podocyte's response to stress: the enigma of foot process effacement

Abstract: Progressive loss of podocytes is the most frequent cause accounting for end-stage renal failure. Podocytes are complex, terminally differentiated cells incapable of replicating. Thus lost podocytes cannot be replaced by proliferation of neighboring undamaged cells. Moreover, podocytes occupy a unique position as epithelial cells, adhering to the glomerular basement membrane (GBM) only by their processes, whereas their cell bodies float within the filtrate in Bowman's space. This exposes podocytes to the danger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
247
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(268 citation statements)
references
References 95 publications
9
247
0
2
Order By: Relevance
“…A previous study showed that signals between slit diaphragm proteins have an important role in the regulation of podocyte function, survival, and actin remodeling (3). Morphological changes in the foot processes of podocytes have been correlated with changes in podocyte cell bodpodocytes with pseudocysts which was found by using TEM and SEM in previous studies (14)(15)(16)25), our results support the idea that damaged podocytes undergo cell-body morphological changes. The present results on podocyte alterations observed by LVSEM are also similar to the findings of previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study showed that signals between slit diaphragm proteins have an important role in the regulation of podocyte function, survival, and actin remodeling (3). Morphological changes in the foot processes of podocytes have been correlated with changes in podocyte cell bodpodocytes with pseudocysts which was found by using TEM and SEM in previous studies (14)(15)(16)25), our results support the idea that damaged podocytes undergo cell-body morphological changes. The present results on podocyte alterations observed by LVSEM are also similar to the findings of previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Adhesion to the glomerular basement membrane (GBM) is a prerequisite of healthy podocytes; detachment from the GBM and loss of podocytes in the urine is a common finding in glomerular diseases. [7][8][9] Despite a growing interest in potential therapeutic strategies to avoid podocyte detachment, there is incomplete knowledge of the dynamic mechanisms that regulate the anchorage of podocyte ramifications to the GBM 7,8,[10][11][12] in order to maintain physiological properties and counteract the continuous mechanical stress due to the high transcapillary filtration pressure. 13 The use of biomaterials offers a unique method to produce surfaces with different nanotopographies and those best fitting cell-specific requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Leakage of plasma proteins in the urine indicates the onset of renal diseases that are associated with podocyte injury (2)(3)(4). Recent evidence has shown that mammalian target of rapamycin (mTOR) 3 signaling activation is an important mediator of diabetic nephropathy in mice and humans (5,6).…”
mentioning
confidence: 99%